Kinematic, bioenergetic and oxidative evaluations of donkey sperm preserved at +4°C. Issue 4 (14th April 2020) - Di Palma, Tommaso; Cecchini, Stefano; Macchia, Giuseppe; Pasolini, Maria Pia; Cocchia, Natascia; Boni, Raffaele
Summary: Information on donkey sperm bioenergetics, kinetics and oxidative status is scarce even though crucial for development of reproductive technologies and germplasm conservation. For these reasons, it is interesting to monitor sperm kinetics, bioenergetics, and oxidative status during sperm storage at +4°C and with several sperm extenders and concentrations. Donkey semen was collected from three jackasses, three times each. It was diluted with four extenders (Kenney, Equiplus, INRA96 or Hippex), set at three sperm concentrations (30, 50 or 70 × 10 6 spermatozoa/ml) and evaluated for its functionality after 0, 3, 24, 48 and 72 h storage at +4°C. Sperm kinetics was analyzed by Sperm Computer Analysis; sperm bioenergetics was assessed by mitochondrial membrane potential (MMP); sperm oxidative status was evaluated by lipid peroxidation (LPO), anti-LPO potential and nitroblue tetrazolium (NBT) assays. Incubation produced a progressive ( P < 0.01) decline in sperm kinetics and MMP, whereas parameters related to oxidative status either increased (LPO, NBT) or decreased (anti-LPO). The anti-LPO potential was the index better related to sperm motility and kinetics. Extenders proved to be differently ( P < 0.01) effective in preserving sperm kinetics, MMP, and oxidative status. The concentration of 30 × 10 6 spermatozoa/ml provided an optimum preservation of sperm functions. Significant correlations emerged between most parameters examined. This study identified reference criteria for storing donkey spermatozoa at +4°C. A low sperm concentration together with a proper extender are crucial requirements for optimum sperm cryopreservation efficiency. Field trials are, however, required to validate these findings, making them operational in practice.